Soybean Flour Supplemented for Nutritional Value Enhancement in Cookies - Vetayasuporn, Sopit; Chanpanya, Sakda; Ramayasamit, Hathaiwan (Koch Cha Sarn Journal of Science, 2024)
Soybean flour was used to substitute wheat flour at different percentage ratios from 0, 25, 50 and 75 for producing cookies. Cookies produced from 75 % substitution of soybean flour gave the highest protein content (13.17 %) and TBA value (0.06), while the highest fat (33.85%), moisture content (2.40 %) and carbohydrate (123.11 µg/ml) were found in the control (100 % wheat flour). During shelf life evaluation of cookies (0, 5, 10 and 15 days) the physical properties were examined and the results showed that moisture content and TBA value increased when their storage time increased.Twenty panelists evaluated the organoleptic characteristics of the cookies, the overall acceptability of control (100 % wheat flour) obtained the highest sensory score at 4.55 followed by 50 % with soybean substitution with sensory score at 4.10.